Comparing the Effectiveness of Cognitive-Behavioral Play Therapy and Resilience-Based Play Therapy on Anxiety, Executive Functioning Behaviors, and Emotional Expression in 6 to 8-Year-Old Children Undergoing Dental Treatment - Hosseini Dastjerdi, Seyed Hasan; Panah Ali, Amir; Azmoudeh, Masoumeh; Molavi, Elaheh (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to compare the effectiveness of cognitive-behavioral play therapy and resilience-based play therapy on anxiety, executive functioning behaviors, and emotional expression in children aged 6 to 8 years undergoing dental treatment.Methods: The current research was a quasi-experimental study with a pre-test, post-test design, including a control group and a two-month follow-up period. All children aged 6 to 8 visiting specialty dental clinics in Isfahan during the first six months of 2021 constituted the research population. Forty-five children were selected using purposive sampling based on inclusion criteria and were randomly assigned to three equal groups of fifteen. Data collection was carried out using the Revised Children's Anxiety Scale - Short Form (Ahlen et al., 2018), the Emotion Expression Questionnaire - Child Form (Penza-Clyve & Zeman, 2002), and the Executive Functioning Questionnaire (Gioia et al., 2000). Cognitive-behavioral play therapy sessions were conducted based on the protocol by Hall, Kaduson, and Schaefer (2002), and resilience-based play therapy sessions followed the protocol by Nikneshan et al. (2019), each lasting for eight weekly sessions of 60 minutes. However, the control group did not receive these interventions. Data analysis was performed using descriptive statistics and mixed ANOVA with SPSS software, version 26.Findings: Results indicated that the mean scores of executive functioning behaviors and their dimensions significantly improved in the experimental groups at post-test compared to the control group, and these improvements remained stable at follow-up (p < 0.05). Moreover, therapeutic interventions (both cognitive-behavioral and resilience-based play therapy) significantly improved scores on anxiety and emotional expressiveness compared to the control group. Additionally, post hoc Bonferroni tests showed that cognitive-behavioral play therapy was more effective than resilience-based play therapy in reducing anxiety scores and increasing skills in emotional expression and executive functioning in children undergoing dental treatment (p < 0.05).Conclusion: These findings further clarify the role of play therapy in children undergoing dental treatment and highlight the necessity of using therapeutic approaches derived from the cognitive-behavioral model to modulate symptoms in these children.